Rapid Assessment Procedure as a Tool for Front-End Stakeholder Needs Analysis in Engineering Projects - Casey Gibson; Jessica Smith; Kathleen Smits; Juan Lucena; Oscar Jaime Restrepo Baena (IEEE Open Journal of Systems Engineering)
Front-end stakeholder needs analysis is increasingly recognized as an essential component of sustainable engineering projects, yet most engineering curricula only cover this topic superficially. Fields such as humanitarian engineering have long recognized the importance of stakeholder needs analysis for the success of development interventions, and researchers have developed best practice frameworks for engaging stakeholders that can be applied to systems engineering. These frameworks rely on established social science techniques, such as ethnography and inductive reasoning, and humanitarian engineering principles, such as contextual listening and sociotechnical thinking, to facilitate comprehensive needs assessments. While conventional ethnographies are often incompatible with engineering projects’ timelines and expertise, anthropologists have developed methodologies to overcome these limitations, such as rapid assessment procedure. While widely applied in the public health sector, rapid assessment procedure has been seldom integrated with engineering projects. Rapid assessment procedure, combined with humanitarian engineering principles, can help researchers quickly gain a nuanced understanding of relevant aspects of complex sociotechnical systems. This article seeks to introduce systems engineers to humanitarian engineering rapid assessment procedure as a concrete technique for conducting comprehensive front-end stakeholder needs analysis. In this article, a case study is presented on the teaching and implementation of humanitarian engineering rapid assessment procedure in a workshop with a group of undergraduate engineering students. We sought to analyze students' perceptions of and learning outcomes from the workshop. Student engagement and learning exceeded expectations, positioning humanitarian engineering rapid assessment procedure as a potentially valuable tool for systems engineers to analyze stakeholder needs to inform system design.